OPTIMALISASI PENGELOLAAN ADMINISTRASI ARSIP DIGITAL DALAM MENINGKATKAN EFISIENSI PELAYANAN PELATIHAN DI BALAI DIKLAT KEAGAMAAN SURABAYA - Devina Fatikhah Putri; Dewi Nur Halimah; Tanto Prima; Sahudi; Lilik Huriyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the optimization strategy of digital archive administration management in improving the efficiency of training services at the Surabaya Religious Training Center. The research method used is descriptive qualitative, with data collection techniques through observation, documentation studies, and in-depth interviews. Data analysis techniques were carried out through data reduction, data presentation, and drawing conclusions. The results showed that the implementation of the Integrated Dynamic Archival Information System (Srikandi) application has transformed conventional bureaucratic flows into digital through automatic manuscript creation, online verification, and the use of electronic signatures. This significantly accelerates the distribution of training information and increases data accountability. Despite technical constraints on the central server, the use of the Ministry of Religious Affairs' Electronic Signature system as a backup line serves as an innovative solution to maintain service continuity. The conclusion of this research is that the optimization of digital archives through the Srikandi application successfully creates administrative efficiencies that support the quality of training services. The innovation of an independent backup system is a distinguishing factor (novelty) that ensures the resilience of bureaucratic services in the digital era.